Transformational Leadership of School Principals - Niwang Tunjung Palupi; Sahrul sahrul; Susmitawati Susmitawati; Sri Pujiyati (Journal of Educational Sciences, 2026)
School principals play a crucial role as heads of educational institutions, serving not only as administrators but also as agents of change. The primary objectives of this study are to evaluate the effectiveness of this leadership model in the field of education, identify the factors influencing its success, and provide practical implications and recommendations for school principals and education policymakers. The research method employed by the researcher is qualitative research using a case study approach to examine the role of transformational leadership by the school principal at SDN 01 Sastrodirjan. The study participants consist of 13 informants: 1 school principal, 10 teachers, and 2 educational staff members. The novelty of this study lies in the principal’s tactics for managing such resistance without triggering open conflict (chaos). The principal did not use formal authority to impose sanctions but instead implemented the “Embracing Through Respect” strategy. In this study, data were collected through interviews, participant observation, and document analysis involving the principal, teachers, and school staff. The research results and discussion indicate that the principal at SD 01 Sastrodirjan in Wonopringgo Subdistrict has applied a transformational leadership style in managing the school.